Importance of TANAP in Competition Between Russia and Central Asia - Varol Sevim, Tugce (International Journal of Energy Economics and Policy, 2013)
TANAP natural gas which was initiated by Azerbaijan’s SOCAR and Turkey’s BOTAŞ has altered the dynamics and strategies in the region. TANAP project not only formed new competition picture from Nabucco versus South Stream to TANAP versus South Stream but also triggered the competition between Russia and Central Asia in terms of pipeline strategies. Kazakhstan, Turkmenistan, and Uzbekistan are landlocked countries in the east Caspian region and Azerbaijan is the only post-Soviet state that had succeeded to reach world markets by non-Russian routes. In this sense if TANAP would establish until 2018-2019, it would have an impact as in the case of Baku-Tbilisi-Ceyhan oil pipeline which was considered as the “Contract of the Century” in the 1990s. In this paper, it is aimed to analyze how TANAP will affect upon Russian foreign energy policy strategy upon Central Asian states and Azerbaijan as well as emphasizing on the risks and opportunities of the project. Keywords: Energy; Natural Gas JEL Classifications: Q49; Q48; Q4